Selection of Pressed Flower Supplier using the Analytic Network Process (ANP) Method - Fadhilah Dirayati; Samsyuryadi Samsyuryadi; Sukemi Sukemi (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2021)
Abstract Supplier has an important role because it will supply material in a long and consistent manner. The difficulty in choosing suppliers is because the company has many suppliers and each of them has advantages and disadvantages. The company requires that the supplied material is of good quality and is delivered on time. Mistakes in supplier selection can be very crucial, because they can have a direct impact on the continuity of the production process. Home Industry Camila is a small industrial company that is engaged in the production of household products. Currently, the company has six suppliers in the procurement of pressed flower raw materials for products made from resin. This study aims to determine the criteria for selecting suppliers and to choose the right supplier so that the risk of supplier selection errors can be minimized. This study uses the Analytic Network Process method with the Super Decisions application. Selection of welding wire supplier involves 6 criteria, 17 sub criteria and 6 alternatives.  Based on the results of data processing, each criterion weight is obtained from the highest value obtained on the delivery criteria (0.2366) and the lowest supplier relationship (0.0309).  This  can  be  interpreted  that  the  delivery  criteria  is  the  most important criterion among other criteria. Meanwhile, the results of the evaluation state that the supplier who chooses the highest weight isGreetings of Grace (GOG) with a criteria weight (0.4491) was then selected as a business partner as a pressed flower supplier in the Camila Home Industry. Keywords : Selection of Supplier and Analytic Network Process (ANP)